Violin jazz in autumn 9 pieces for violin and piano - Iles, Nikki 1963- (Oxford Oxford University Press, 2016)
"With fully notated rhythms, grooves, and improvisations, Violin Jass in Autumn is the perfect collection for instrumentalists looking for that authentic sound."--Back cover.
(Somewhere) Over the rainbow -- Hay barn blues -- Autumn leaves -- Des vendanges -- Here's that rainy day -- Danny boy -- Harvest calypso -- September in the rain -- Gypsy waltz.
Accompanying CD includes full performance and backing-only tracks.
Arranger's note in English.
Keywords: Violin and piano music, Arranged -- Scores and parts; Violin and piano music -- Scores and parts; Jazz